Seismicity located by the National Seismological Network during 2022 - Linkimer, Lepolt (2023)
During 2022, the National Seismological Network (RSN) located 4763 local earthquakes, which is equivalent to the seismic energy released by an earthquake of moment magnitude (Mw) 7.0. The epicenters were mainly concentrated in nine areas with 25-400 events. A total of 184 earthquakes (~4 % of the total) were felt by the population, including 19 with Mw between 5.0 and 6.7. Most of these events were shallow (~87 % < 30 km), of low magnitude (~52 % Mw < 3.9), and originated by faults in the Caribbean and Panama plates (~52 %). The largest earthquake of the year, Mw 6.7, was related to the subduction of the Nazca plate and generated the highest reported intensity of V in Burica. High intensities were not reported because all of the Mw ≥ 5.5 earthquakes were located offshore and far from populated centers.